Molecular docking and molecular dynamic simulation of 1,3-Benzoxazine derivatives against penicillin binding protein 2A of methicillin-resistant Staphlyococcus aureus - Alharbi, Nourah Jamaan H (2023)
Methicillin-resistant Staphylococcus aureus (MRSA) has a penicillin-binding protein 2a encoded by mecA localized on staphylococcal cassette chromosome mec (SCCmec). MRSA has six different types that show resistance to all β- lactam antibiotics. Patients with MRSA infections have higher healthcare costs, have to stay longer in hospital, and eventually died. 1,3-Benzoxazine is a class of heterocyclic compounds that act as antibacterial agents. The molecular docking analyses, molecular dynamics (MD) simulations, dynamic crosscorrelation matrix (DCCM) and Molecular mechanics Poisson-Boltzmann surface area (MM-PBSA) were performed to investigate the interactional analyses of PBP2a against the derivatives of 1,3-benzoxazine. Twenty (20) 1,3- benzoxazine derivatives were subjected to molecular docking analyses using MOE software. Moreover, eight previously synthesized symmetrical 1,3- benzoxazine compounds (21-28) with known activities against Staphylococcus aureus, along with twelve newly designed compounds (29-40), were also utilized. The molecular docking results revealed that the 3,4-dihydro-2H-1,3- benzoxazine containing 5-methylisoxazole group (compound 28) showed the least binding energy among the synthesized compounds. Interestingly, it was observed that the 3,4-dihydro-2H-1,3-benzoxazine containing a 5-(4- fluorophenyl) isoxazole group (compound 38) showed lowest binding energy among the newly modified 1,3-benzoxazines. MD simulation was performed for the selected targets, and top ranked compounds, 28 and 38, were reported. The results of MD analysis confirmed the stability of the penicillin binding protein-2a/ ligand 38 complex based on the results of root-mean-square deviation (RMSD), radius of gyration (Rg), and solvent accessible surface area (SASA) analysis, unlike ligand 28. The root-mean-square fluctuations (RMSF) results revealed that amino acid fluctuation of binding pocket residues was not observed upon binding of ligand 38. The binding analysis showed that ligand 28 disturbs the conformational space of the amino acid residues, whereas ligand 38 only affects the non-local contacts. The hydrogen bond analysis of ligand 38 showed the highest occupancy of hydrogen bond formation with amino acid Asn-545 (84.0